Development of a Supplementary Ecosystem Booklet for 10th Grade High School Students: A Case Study of Mangrove Edupark Tambakrejo - Handayani, Nur Anis; Putut Martin (Universitas Negeri Semarang, 2025)
This study aims to develop a biology learning supplement based on the local potential of the surrounding school area, specifically the Mangrove Edupark Tambakrejo Semarang, and to improve the learning outcomes of 10th-grade high school students. The research method used in this study is an adaptation of the 4D model developed by Thiagarajan, modified to only be implemented in the research location. This study involved 45 students from two classes as research subjects, selected through purposive sampling at SMA Sultan Agung 3 Semarang. The results showed that the Mangrove Edupark-based ecosystem booklet is feasible to use as a learning supplement and can improve students' learning outcomes. The practical implication of this study is that the ecosystem booklet can be an effective alternative to support biology learning in 10th grade and enhance students' creative thinking skills through meaningful learning, allowing students to better recognize the environmental wisdom around them. However, this study has limitations in terms of sample distribution, which is limited to only one school, and the incompleteness of the material content. Therefore, future research can involve more school samples around the Mangrove Edupark Tambakrejo area and improve the ecosystem material content to be more comprehensive.